2018
DOI: 10.1016/j.anifeedsci.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flavonoids extracted from Citrus aurantium on performance, eating and animal behavior, rumen health, and carcass quality in Holstein bulls fed high-concentrate diets

Abstract: Feed Science and Technology © Elsevier after peer review. To access the final edited and published work see https://doi.org/10.1016/j.anifeedsci.2018.08.010 FLAVONOIDS AND RUMEN HEALTH AND PERFORMANCE 1 2 Effects of flavonoids extracted from Citrus aurantium on performance, eating and 3 animal behavior, rumen health, and carcass quality in Holstein bulls fed high-4 concentrate diets. 5 6 MABSTRACT 22The effects of flavonoids extracted from Citrus aurantium (Bioflavex® CA) on eating 23 pattern, performance, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 45 publications
8
31
0
Order By: Relevance
“…Supplementation with citrus flavonoids reduced agonistic behaviors throughout the fattening period, and sexual interactions during the finishing phase in past studies (Paniagua et al, 2018). The mechanisms whereby citrus flavonoids may modulate eating and animal behavior are unknown.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Supplementation with citrus flavonoids reduced agonistic behaviors throughout the fattening period, and sexual interactions during the finishing phase in past studies (Paniagua et al, 2018). The mechanisms whereby citrus flavonoids may modulate eating and animal behavior are unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Flavonoids are polyphenols that have been deeply studied, and Citrus fruits are considered the major source of flavonoids, containing a wide range of these phytochemicals. Recently, Paniagua et al (2018) studied in Holstein bulls fed highconcentrate diet the effect of an extract from bitter orange (Citrus aurantium) rich in naringin during the growing and finishing phase. Bulls supplemented with citrus flavonoid extract modified their eating pattern, by reducing large meal sizes (>750 g/ meal) and spending more time eating straw, and rumen wall health parameters analyzed were improved.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous results, no effect of an extract of plant flavonoids (Bioflavex; 300 mg kg −1 ) on feed intake of heifers consuming high-concentrate diets was observed. 8 On the other hand, Paniagua et al 10 found a significant decrease in the daily concentrate intake of Holstein bulls fed a diet supplemented with flavonoids extracted from Citrus aurantium (Bioflavex; 0.4 g kg −1 ) over a period of 112 days. However, even in this experiment this difference disappeared in the last 8 weeks of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…an increase in lactate‐consuming bacteria and the depression of methanogenic archaea communities. The average daily gain and feed conversion ratio were not significantly influenced after the addition of Bioflavex in the diets of heifers at the level of 0.3 g kg −1 and bulls at the level of 0.4 g kg −1 . However, the nature of each plant secondary metabolite and the diet composition (e.g., forage to concentrate ratio, ingredients used in the ration, tropical versus temperate forages) appeared to influence the efficacy of their in vivo application on the examined parameters of dairy cows .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation